Measurement technique of calcaneal varus from axial view radiograph - Thossart Harnroongroj (2018)
Background: Medial displaced posterior calcaneal tubercle creates varus deformity of an intraarticular calcaneal fracture. The fracture involves posterior calcaneal facet and the calcaneal body so we developed a measurement technique representing the angle between posterior facet and long axis of calcaneus using lateral malleolus and longitudinal bone trabeculae of posterior calcaneal tubercle as references to obtain calcaneal varus angle. Materials and Methods: 52 axial view calcaneal radiographs of 26 volunteers were studied. Angles between posterior facet and long axis of calcaneus were measured using the measurements 1 and 2. Angle of measurement 1, as gold standard, was obtained from long axis and posterior facet of calcaneus whereas measurement 2 was obtained from a line, perpendicular to apex curve of lateral cortex of the lateral malleolus and a line parallel to the longitudinal bone trabeculae of posterior calcaneal tubercle. No more than 3° of difference in the angle of both measurements was accepted. Reliability of the measurement 2 was statistically tested. Results: Angles of measurement 1 and 2 were 90.04° ± 4.00° and 90.58° ± 3.78°. Mean of different degrees of both measurements was 0.54° ± 2.31° with 95% of confidence interval: 0.10°-1.88°. The statistical analysis of measurement 1 and 2 showed more than 0.75 of ICC and 0.826 of Pearson correlation coefficient. Conclusion: Technique of measurement 2 using lateral malleolus and longitudinal bone trabeculae of posterior calcaneal tubercle as references has strong reliability for representing the angle between long axis and posterior facet of calcaneus to achieve calcaneal varus angle.